Coasting Through the Age of Steam: Commerce and Community along the Gulf Coast - Grubbs, Kevin (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
This article examines the persistence of the Gulf Coast’s coasting trade during the late nineteenth century, revealing how sail and steam coexisted within a shared maritime world. Coasting schooners linked small ports, islands, and inland markets, sustaining older traditions of labor and community even as industrialization reshaped global trade. By tracing these local networks of work and exchange, the article argues that maritime modernity along the Gulf was uneven and negotiated rather than uniform. The Gulf emerges as a liminal space where sea and shore, sail and steam, and tradition and modernity continuously intersected.